Business Model of Integrated Healthcare Clinic in Sikhio District, Nakhon Ratchasima Province - Wayuphak, Sireetorn; Jarernsiripornkul, Sakchai (MBA-KKU Journal, 2023)
This study aims to study healthcare behavior, Attitudes toward alternative medicine and traditional Chinese medicine, and marketing mix factors influencing interest in healthcare in Sikhio District, Nakhon Ratchasima Province, to study the external business environment and to define a business model. Data from the questionnaire was accidentally sampled and analyzed by descriptive statistics. The results showed that Modern medicine is a significant threat to most healthcare behaviors. Receive advice on using herbs and alternative medicine to maintain health from friends/acquaintances. Attitudes towards alternative medicine and traditional Chinese medicine found that there were agreeing and marketing mix factors influencing interest in healthcare. For the business model are as follows: 1) Customer Segments are people aged 40 years and over residing in Sikhio municipality and nearby areas. 2) Value proposition offers a new healthcare alternative with various treatment services. 3) Customer relationships to organize health promotion activities. There is public relations through social media. 4) Channels, divided into offline channels and online channels. 5) Cost structure the total cost is 5,405,350.60 baht. 6) Key activities are multi-clinic services 7) Key resources include health clinics, funds, doctors and personnel, medicines, equipment, and tools that are Used to treat 8) Key partners, financial institution Suppliers of medical devices and equipment, medicine, including social media service providers and 9) Revenue streams, in the first year the income was 2,003,400.00 baht.